Dehydrogenative α-Oxygenation of Cyclic Ethers by a High-Valent Manganese(IV)-Oxo Species - Muhammad Qadri Effendy Mubarak; Hafiz Saqib Ali; Jimei Zhou; Chaoqun Li; Jianliang Xiao; Sam P. Visser (John Wiley & Sons, Ltd, 2024)
Indexed by SCOPUS/ERA